1981
DOI: 10.3382/ps.0602284
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Healthy and Eimeria acervulina-lnfected Chicks as Influenced by Anticoccidial Drugs and Source of Dietary Protein

Abstract: Four experiments were conducted to evaluate an alleged interaction between the anticoccidial drugs, monensin and lasalocid, and dietary protein source. Chicks were fed practical diets (approximately 24% crude protein) containing from 0 to 13% animal-source protein supplied by either a fish meal-meat and bone meal combination or by feather meal. Monensin (121 mg/kg) and lasalocid (125 mg/kg) were evaluated for anorexigenic activity in health birds and for growth-enhancement activity in E. acervulina-infected bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
(10 reference statements)
2
6
0
Order By: Relevance
“…Cervantes et al (1981) recently found that dietary potassium level accounted for differences in monensin toxicity between diets with or without large amounts of animal protein. In contrast, Willis and Baker (1981) observed no effect on growth rate from adding potassium to a 13% animal protein diet calculated to contain .73% potassium. In our study, the calculated potassium level of the diet decreased as protein level was reduced, because soybean meal contains more potassium than corn (2.02 vs. .45%, respectively; National Research Council [NRC], 1977).…”
Section: Discussionmentioning
confidence: 50%
“…Cervantes et al (1981) recently found that dietary potassium level accounted for differences in monensin toxicity between diets with or without large amounts of animal protein. In contrast, Willis and Baker (1981) observed no effect on growth rate from adding potassium to a 13% animal protein diet calculated to contain .73% potassium. In our study, the calculated potassium level of the diet decreased as protein level was reduced, because soybean meal contains more potassium than corn (2.02 vs. .45%, respectively; National Research Council [NRC], 1977).…”
Section: Discussionmentioning
confidence: 50%
“…When the high fish meal diet was supplemented with .3% potassium, the chicks' growth response to monensin was similar to that seen in the chicks fed a cornsoybean meal or a high fish meal ration without monensin. and K, and data reported by Willis and Baker (1981) indicated a counteraction by K of depression in gain/feed ratio observed with monensin. Early Rb and K interaction studies at Colorado State University (Sasser et al, 1969) showed that adding Rb to K-deficient diets significantly depressed chick growth and increased mortality.…”
Section: Introductionsupporting
confidence: 44%
“…Because females exhibit a higher feed intake per body weight gain, this would result in a higher milligram dose rate per body weight gain of anticoccidial and thus possibly exacerbate weight depression in the females. Several reports have concluded that ionophore medications can depress body weights through reduced feed intake (Morrison et al, 1979;Patel et al, 1980;Willis and Baker, 1981), but other studies have found no effect (Frigg and Broz, 1983;Gard et al, 1975). These contradictory findings may be partially atrributable to differing levels of medication.…”
Section: Discussionmentioning
confidence: 95%
“…1980), although this latter interaction has been demonstrated to be of little practical significance (Willis and Baker, 1980). More recently, Willis and Baker (1981) were unable to detect interactions between monensin or lasalocid with source of dietary protein. Reports have also surfaced from the commercial broiler industry of wet pen litter with the feeding of lasalocid (Ward and Brewer, 1981) possibly due to the ionophores influence upon acid-base relationships and proper osmotic balance.…”
Section: Introductionmentioning
confidence: 92%